Monetary Concepts and Definitions. (IMF Working Papers; Working Paper ;, 1989)
This paper examines monetary concepts and definitions. It notes that approaches to monetary analysis, and the concept of money itself, have been undergoing substantial change in many countries due in large part to recent innovation, which has affected financial markets, financial instruments, and financial institutions. As a result, many countries increasingly tend to focus on multiple creators and instruments of money as opposed to just currency and transferable demand deposits. This fact is borne out by the paper's survey of national practices in the selection and grouping of instruments in money measures. The paper concludes that the emerging trend towards broader concepts of money implies the need for some rethinking of traditional notion of money measures.